Concluding remarks - Mohd Razman, Mohd Azraai; Abdul Majeed, Anwar P.P.; Musa, Rabiu Muazu; Taha, Zahari; Susto, Gian Antonio; Mukai, Yukinori (Springer, 2020)
The established automatic request feeder was able to understand the objective of this study through which to collect meaningful data without neglecting any vital information, including the feeding time, the feeder cause between the hungry and the happy, and the most relevant, extracting the notable features of the fish movement behaviours across the test. The contribution and future work shall be drawn up in conjunction with the goals reached in this report.